Bone marrow-derived mesenchymal stem cells transplantation alters the course of experimental paracoccidioidomycosis by exacerbating the chronic pulmonary inflammatory response (2018)
ABSTRACT: Several studies have shown the potential use of bone marrow mesenchymal stem cells (BM-MSCs) as a therapeutic approach to infectious diseases. Since BM-MSCs can exert antimicrobial properties and influence the immune response against pathogens, our aim was to study the antimicrobial therapeutic potential of BM-MSCs in an experimental model of paracoccidioidomycosis (PCM). BM-MSCs were isolated from BALB/c donor mice. Paracoccidioides brasiliensis–infected male BALB/c mice were injected with purified BM-MSCs at 8th week post-infection. Mice were sacrificed at 12th week postinfection. Homing of BM-MSCs was confirmed by cellular labeling with fluorescent lipophilic dye and detected by flow cytometry. We found that, in comparison with nontransplanted infected animals, BM-MSCs-treated and P. brasiliensis-infected mice showed a significant increase in (i) fungal burdens, (ii) neutrophils, eosinophils and M2 macrophages counts, and (iii) interleukin (IL)-6, IL-9, GM-CSF, CXCL1, CXCL9, and CCL5 levels, while presenting a decrease in M1 macrophages and Treg cells in lungs. In addition, the histopathological analysis of the lungs showed an increased inflammatory process. This is the first study to our knowledge that evaluates the effects of BM-MSCs treatment in PCM. Our results indicate that the immunoregulatory function of BM-MSCs may be triggered by the interaction with P. brasiliensis, which exacerbates chronic pulmonary inflammatory response.